Making a Difference for All Kansans 2012 Report to the Legislature - Pierzynski, Gary M. (My University, 2012)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2012, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN26_2012_01
Keywords: UNN26; Administrative and Research Reports; legislature